Endothelial KCa channels: Novel targets to reduce atherosclerosis-driven vascular dysfunction - Vera, O. Daniel; Wulff, Heike; Braun, Andrew P. (Frontiers in Pharmacology, 2023)
Elevated levels of cholesterol in the blood can induce endothelial dysfunction, a condition characterized by impaired nitric oxide production and decreased vasodilatory capacity. Endothelial dysfunction can promote vascular disease, such as atherosclerosis, where macrophages accumulate in the vascular intima and fatty plaques form that impair normal blood flow in conduit arteries. Current pharmacological strategies to treat atherosclerosis mostly focus on lipid lowering to prevent high levels of plasma cholesterol that induce endothelial dysfunction and atherosclerosis. While this approach is effective for most patients with atherosclerosis, for some, lipid lowering is not enough to reduce their cardiovascular risk factors associated with atherosclerosis (e.g., hypertension, cardiac dysfunction, stroke, etc.). For such patients, additional strategies targeted at reducing endothelial dysfunction may be beneficial. One novel strategy to restore endothelial function and mitigate atherosclerosis risk is to enhance the activity of Ca2+-activated K+ (KCa) channels in the endothelium with positive gating modulator drugs. Here, we review the mechanism of action of these small molecules and discuss their ability to improve endothelial function. We then explore how this strategy could mitigate endothelial dysfunction in the context of atherosclerosis by examining how KCa modulators can improve cardiovascular function in other settings, such as aging and type 2 diabetes. Finally, we consider questions that will need to be addressed to determine whether KCa channel activation could be used as a long-term add-on to lipid lowering to augment atherosclerosis treatment, particularly in patients where lipid-lowering is not adequate to improve their cardiovascular health.